Analisis Timbulan Sampah Domestik Di Kota Dumai - Rifad Andrian Saragih; Jecky Asmura; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Dumai City has an administrative area of 1,727.38 km2, consisting of 7 districts, namely Dumai Kota, Dumai Timur, Dumai Barat, Dumai Selatan, Bukit Kapur, Medang Kampai, Sungai Sembilan. In 2018 the population density was 176 people / km2 and the population growth rate was 2.74%. With a population of 303,292 people, the city of Dumai has the potential to produce large amounts of waste, which if not managed properly can cause a decrease in the quality and aesthetics of the environment. Therefore it is necessary to calculate the generation of waste as a basis for waste management in the city of Dumai. The calculation of waste generation that is carried out refers to SNI 19-3964-1995, the unit of large city waste generation = 2 - 2.5 L / person / day, or = 0.4 - 0.5 kg / person / day, the unit of waste generation medium / small city = 1.5 - 2 L / person / day, or = 0.3 - 0.4 kg / person / day. Based on the results of the calculation of waste generation, dumai city is included in the category of medium cities, it is found that the waste generation is 606,5 m3 / day. Key words: dumai city, waste generation, domestic waste.